Bio-Monitoring and Occupational Risk Assessment in Human Population from Nuclear Research Centre - using Exfoliated Buccal Epithelial Cells and Peripheral Blood Lymphocytes - Sharma, N. K.; Kamble, S. D.; Jeyaprakash, D. (Current Overview on Disease and Health Research Vol. 2, 2022)
The study is aimed to investigate and compare the baseline frequency of the micronucleus in exfoliated buccal epithelial cells (BE cells) and peripheral blood lymphocytes of the same subjects in random human population of nuclear research centre. The need of the hour is for a noninvasive way to evaluate radiation and mutagen exposure. The buccal epithelial micronuclei assay was assessed for this purpose by monitoring staff of our nuclear research centre, those who came in for their annual medical examination. The micronucleus assay is a sensitive indicator that measures chromosomal breakage, damage, and loss. . A study was undertaken for evaluating 50 random individuals working in nuclear research centre, to compare baseline micronuclei frequency in exfoliated buccal epithelial cells and lymphocyte micronuclei. Buccal micronucleus cytome assay (BMNcyt) and blood lymphocyte cytokinesis blocked micronuclei assay (CBMN) was performed on slides stained with Geimsa’s stain. We report the mean frequency of spontaneous micronuclei in buccal epithelial cells and blood lymphocytes. The mean Frequency of micronuclei (MN) observed in buccal epithelial cells of females 0.99 ± 0.21 ‰ (range 0.09 to 2.92) and of males 0.49 ± 0.10 ‰ (range 0.00 to 2.06). MN frequency in buccal epithelial cells was 0.66 ± 0.10 ‰ (range 0.00 to 2.92). The MN frequencies in human peripheral blood lymphocytes of same donors were found to be 8.61 ± 0.10 ‰ (range 3.00 to 17.00) in females and 9.15 ± 1.00 ‰ (range 3.00 to 22.00) in males. A total MN frequency in cytokinesis blocked lymphocytes was 8.96 ± 0.73 ‰ Bi-nucleated (BN) cells (Range: 3.00 to 22.00). The observed baseline frequency of spontaneous micronuclei in buccal epithelial cell and in human peripheral blood lymphocytes are correlating. Therefore buccal epithelial cell micronuclei are a good noninvasive bio-monitoring assay.